Experimental study of the physical and mechanical properties of particleboard reinforced with eggshell, wood, and bamboo hybrid fillers - Sunardi Sunardi; Thairq Al Aziz Pratama; Mekro Permana Pinem; Yusvardi Yusuf; Agung Sudrajad; Indar Kustiningsih (Jurnal Polimesin, 2026)
The use of natural resources as particleboard materials has significantly increased due to growing environmental and sustainability concerns. This study aims to evaluate the physical and mechanical properties of particleboard made from three waste materials: eggshell particles, wood particles, and bamboo particles. The composite was formulated with the volume fractions of 10% epoxy resin, 25% Polyvinyl Acetate (PVAc) adhesive, 40% eggshell particles, and a 25% combined bamboo and wood particles. The bamboo-to-wood ratios investigated were 0:25 (B0W25), 12.5:12.5 (B12.5W12.5), and 25:0 (B25W0). Samples were prepared by cold compaction at 3 MPa for 2 hours, followed by curing at 100°C for 1 hour. The samples were evaluated for various physical properties, including density, water absorption, and thickness swelling, as well as mechanical properties such as hardness, flexural strength, flexural modulus, and flexural strain. Since multiple responses were obtained, the Data Envelopment Analysis-based Ranking (DEAR) method was used to assess composite performance. The study found that sample B25W0 exhibited the most optimal performance, with a density of 1.53 ± 0.01 g/cm³, water absorption of 8.47 ± 0.36%, thickness swelling of 6.05 ± 0.89%, hardness of 67.17 ± 0.94 Shore D, flexural strength of 12.90 ± 0.29 MPa, flexural modulus of 1.24 ± 0.03 GPa, and flexural strain of 2.23 ± 0.17%. The improvement is attributed to the alkali treatment of the bamboo particles. These results indicate that eggshell and bamboo hybrid fillers have strong potential as for structural particleboard.